The Teaching Style of English Teachers in Maintaining Students’ Motivation in Learning English at SMA Negeri 1 Enrekang - Jabri, Umiyati (Universitas Muhammadiyah Enrekang, 2019)
Purposes: This research aimed at finding the teaching style by English teachers in teaching English to second grade students at SMAN 1 Enrekang, teaching styles that second grade students of SMAN 1 Enrekang favor, and whether the teaching style of the teachers of English maintain the motivation of the second grade students. Methodology: The sample consisted of two teachers and 30 students in two classes. In this research, the data were obtained through three kinds of instruments namely, observation checklist, questionnaire, and interview. Findings: The result showed that the teaching style of English teacher of XI IPA 3 was auditory while the English teacher of XI IPS 1 was visual auditory, both two classes of XI IPA 3 and XI IPS 1 favored kinesthetic visual teaching style, and the teachers could maintain the motivation of both two classes based on the result of mean score showed that it was positive. The result of questionnaire calculation of XI IPA 3 students was 94.5 with the mean was 3.94. The result of questionnaire calculation of XI IPS 1 students was 95.4 with the mean was 3.97. Implication: The results were considered to be positive as stated in Likert Scale.